2014
DOI: 10.7314/apjcp.2014.15.2.617
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-Inducing Activity of HPLC Fraction from Voacanga globosa (Blanco) Merr. on the Human Colon Carcinoma Cell Line, HCT116

Abstract: likely to produce anti-cancer compounds. Using MTT assay, the study aimed to test HPLC fractions from the V globosa leaf extract for cytotoxicity against the HCT116 human colon carcinoma, A549 human lung carcinoma and the non-cancer AA8 Chinese hamster ovarian cell lines. Possible pro-apoptotic activity was also assessed using DAPI nuclear staining, TUNEL assay and the JC-1 mitochondrial membrane potential assay. Production of the ethanolic crude extractMature leaves from V globosa (Blanco) Merr. wereInstitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…This was supported by translocation of PS to outer surface of PM (Fadok et al, 1998) under microscopy, the DNA damage (Nagata, 2000) induced in comet assay also clearly suggest that the seed extract has therapeutic value against cancer cells. The anti-cancer potential of Carissa spinarum (Sehar et al, 2011, Rao et al, 2005), Wrightia tomentosa (Chakravarti et al, 2012) and several other members of Apocynaceae have also previously been documented (Acebedo et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…This was supported by translocation of PS to outer surface of PM (Fadok et al, 1998) under microscopy, the DNA damage (Nagata, 2000) induced in comet assay also clearly suggest that the seed extract has therapeutic value against cancer cells. The anti-cancer potential of Carissa spinarum (Sehar et al, 2011, Rao et al, 2005), Wrightia tomentosa (Chakravarti et al, 2012) and several other members of Apocynaceae have also previously been documented (Acebedo et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…An increase in Bax relative to Bcl-2 promotes release of cytochrome C from the mitochondria with subsequent activation of caspase-3, thereby inducing mitochondrial mediated apoptosis (Gupta and DuBois, 2001). Natural compounds has the ability to induce cytotoxicity thereby protects against cancer and many researcher's developing chemotherapeutic by based on its ability to induce apoptosis (Sriram et al, 2008;Acebedo et al, 2014;Shafie et al, 2013b;Zou et al, 2013). Lim et al (2012) reported that luteolin induce cell cycle arrest and apoptosis in HT-29 human colon cancer cells.…”
Section: Luteolin Effects On Apoptosismentioning
confidence: 99%
“…Many genetic and epigenetic factors play a role in this process. Apoptosis is one of these factors (Li et al, 2013;Zhu et al, 2013;Acebedo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%